Implications of productivity and nutrient requirements on greenhouse gas balance of annual and perennial bioenergy crops. Issue 4 (12th April 2013) - Cadoux, Stephane; Ferchaud, Fabien; Demay, Charlotte; Boizard, Hubert; Machet, Jean‐Marie; Fourdinier, Emilie; Preudhomme, Matthieu; Chabbert, Brigitte; Gosse, Ghislain; Mary, Bruno
Abstract Biomass from dedicated crops is expected to contribute significantly to the replacement of fossil resources. However, sustainable bioenergy cropping systems must provide high biomass production and low environmental impacts. This study aimed at quantifying biomass production, nutrient removal, expected ethanol production, and greenhouse gas (GHG) balance of six bioenergy crops: Miscanthus × giganteus, switchgrass, fescue, alfalfa, triticale, and fiber sorghum. Biomass production and N, P, K balances (input‐output) were measured during 4 years in a long‐term experiment, which included two nitrogen fertilization treatments. These results were used to calculate a posteriori 'optimized' fertilization practices, which would ensure a sustainable production with a nil balance of nutrients. A modified version of the cost/benefit approach proposed by Crutzen et al. (2008), comparing the GHG emissions resulting from N‐P‐K fertilization of bioenergy crops and the GHG emissions saved by replacing fossil fuel, was applied to these 'optimized' situations. Biomass production varied among crops between 10.0 (fescue) and 26.9 t DM ha−1 yr−1 (miscanthus harvested early) and the expected ethanol production between 1.3 (alfalfa) and 6.1 t ha−1 yr−1 (miscanthus harvested early). The cost/benefit ratio ranged from 0.10 (miscanthus harvested late) to 0.71 (fescue); it was closely correlated with the N/C ratio of the harvested biomass, except for alfalfa. The amount of saved CO2 emissions varied from 1.0 (fescue) to 8.6 t CO2eq ha−1 yr−1 (miscanthus harvested early or late). Due to its high biomass production, miscanthus was able to combine a high production of ethanol and a large saving of CO2 emissions. Miscanthus and switchgrass harvested late gave the best compromise between low N‐P‐K requirements, high GHG saving per unit of biomass, and high productivity per hectare.